Post-partum and non-post-partum relapsing Graves' hyperthyroidism display different response to anti-thyroid drugs. Issue 6 (June 2018) - Rotondi, Mario; Capelli, Valentina; Coperchini, Francesca; Pinto, Sara; Croce, Laura; Tonacchera, Massimo; Chiovato, Luca
Abstract : Design: Graves' disease (GD) patients in remission after a full course of methimazole (MMI) therapy are at risk for a relapse of hyperthyroidism during the post-partum (PP) period, but whether this relapse may display any peculiarity is still unknown. Aim of this study was to compare GD patients undergoing a relapse of hyperthyroidism either in the PP period or not. Methods: We retrospectively evaluated forty-three GD female patients in their childbearing age who experienced a relapse of hyperthyroidism. Eighteen of them relapsed in the PP period (i.e. within 12 months after delivery, PP group); the remaining 25 relapsed elsewhere during life (NPP group). Results: Age at relapse, thyroid volume, thyroid function tests, TRAb titers, smoking habit, presence and degree of orbitopathy and duration of methimazole (MMI) treatment did not differ in the two groups. However, the remission rate was much greater (79%) in the PP as compared with the NPP (32%) group ( P = 0.002). A significant reduction in TRAb levels occurred at 12-month MMI treatment in the PP ( F = 9.016; P = 0.001), but not in the NPP group ( F = 2.433; NS). At 12 months, the PP group had significantly lower mean TRAb levels (0.6 ± 1.1 U/L and 4.5 ± 4.7 U/L in the PP and the NPP group, respectively; P = 0.029). Conclusions: Relapsing Graves' hyperthyroidism in the PP period is more prone to undergo a remission after a second course of MMI treatment. In these patients, a conservative therapeutic approach is more appropriate.